Newly synthesized Cu(II) pyrazino[2,3-f][1,10]phenanthroline complexes as potential anticancer candidates - Inci, Duygu; Aydin, Rahmiye; Huriyet, Huzeyfe; Zorlu, Yunus; Cinkilic, Niluefer (Wiley, 2018)
New binary and ternary copper(II) complexes, [Cu(py-phen)(2)(NO3)]NO3 (1), [Cu-2(py-phen)(2)(gly)(2)(NO3)(2)(H2O)(2)]3H(2)O (2) and [Cu-2(py-phen)(2)(tyr)(2)(H2O)(2)](NO3)(2)3H(2)O (3) (py-phen: pyrazino[2,3-f][1,10]phenanthroline; gly: glycine; tyr: tyrosine), have been synthesized and characterized using CHN analysis, electrospray ionization mass spectrometry, Fourier transform infrared spectroscopy and single-crystal X-ray diffraction. Interaction of these complexes with calf thymus DNA has been investigated using absorption spectral titration, ethidium bromide and Hoechst 33258 displacement assay and thermal denaturation measurements. These complexes were found to be efficient cleaving agents and cleavage reactions were mediated by hydrolytic and oxidative pathways. The interaction between these complexes and bovine serum albumin (BSA) was investigated using electronic absorption and fluorescence spectroscopy. The experimental results show that the fluorescence quenching mechanism of these complexes and BSA is a static quenching process. Furthermore, in vitro cytotoxicities of these complexes against tumour cell lines (Caco-2, MCF-7 and A549) and healthy cell line (BEAS-2B) showed that they exhibited anticancer activity with low IC50 values. These complexes were markedly active against the cell lines and can be good drug candidates that are effective and safe for healthy tissue.
Keywords: Cu(II) complexes; cytotoxicities; DNA; BSA interactions; glycine; pyrazino[2; 3-f][1; 10] phenanthroline; amino acids